Translation and Chaos: Poetry Translators' Agency in a Non-Hegemonic Network. A Digital Humanities Approach. - Tanasescu, Raluca Andreia (Université d'Ottawa / University of Ottawa, 2018)
This project examines the role played by chaos in shaping and defining the translation activity in a non-hegemonic context, with a focus on literary translation. Based on English-language U.S. and Canadian contemporary poetry translation into Romanian between 1960 and 2017, it challenges the ‘major’ vs. ‘minor’ dichotomy and moves to show that a transnational framework and a networked understanding of translator agency are much better suited to account for the complexity of a translation sociography. Acknowledging a necessary shift that draws on an economy of attention more than on an economy of production (Cronin 2016), as well as on Michael Cronin’s politics of microspection and on Kobus Marais’ paradigm of complexity (2014), my work takes distance from the Bourdieusian dynamics of power that has prevailed in translation studies since the late 1990s and favors a network approach that accounts for disruption, decentralization, and voids. This dissertation seeks to acknowledge the role played by chance, chaos, and self-regulation in shaping the activity of literary translation through the deployment of a mathematical model that has been at the core of Web 2.0 since its very inception. In doing so, my research sets out to complement Bruno Latour’s Actor-Network-Theory with the mathematical notions of network and network of networks. I endeavor to explore the webs of connectivity as they appear in real-life contemporary poetry translator networks with the purpose of potentially laying the groundwork for a possible redefinition of translation across society and media of circulation. Translation can be conceived, I propose, as an act that is essentially, simultaneously and irreducibly linguistic, cultural, and social, but also individual and collective, material and virtual, online and offline. Under these circumstances, I conclude that a critical re-examination of translation studies in micromodernity through a Digital Humanities lens becomes necessary, if not imperative.
Keywords: Digital humanities; Chaos theory; Networks; Literary translation; Translator's agency; Translation studies